TRANSFORMATION OF EDUCATORS’ PROFESSIONALISM IN THE SYSTEM OF POST-GRADUATE TEACHER EDUCATION - Tamara Sorochan (Education: Modern Discourses, 2018)
The article analyzes the application of the theory of transformative education in post-graduate teacher education. Professional development of teachers, which is based on the principles of adult education, is influenced by education reforms, innovation environment and the transition to a digital society. This creates a situation of uncertainty for teachers and encourages their acquisition of new competences. Transformational education, initiated by US scholars, has gained popularity in Ukraine to direct post-graduate education to the development of professional culture and professional consciousness of teachers. One of the key concepts of post-graduate teacher education as a component of adult education is professionalism, which is referred to as a set of teachers’ competences that are formed in the system of university education and developed in the system of post-graduate education based on cultural, humanistic and democratic values to make teachers efficient in modern socio-economic conditions. Teachers’ professionalism transformation, which is understood as a qualitative change in their professionalism, due to their readiness to work in the conditions of the digital world and knowledge society, is a result of transformative education in the system of formal and informal adult education. The author also discusses the teachers’ professionalism transformation factors and the features, methods, objectives and outcomes of teachers’ transformative education.